Addressing the Crisis in the Treatment of Osteoporosis: A Path Forward. (17th January 2017) - Khosla, Sundeep; Cauley, Jane A; Compston, Juliet; Kiel, Douglas P; Rosen, Clifford; Saag, Kenneth G; Shane, Elizabeth
ABSTRACT: Considerable data and media attention have highlighted a potential "crisis" in the treatment of osteoporosis. Specifically, despite the availability of several effective drugs to prevent fractures, many patients who need pharmacological therapy are either not being prescribed these medications or if prescribed a medication, are simply not taking it. Although there are many reasons for this "gap" in the treatment of osteoporosis, a major factor is physician and patient concerns over the risk of side effects, especially atypical femur fractures (AFFs) related to bisphosphonate (and perhaps other antiresorptive) drug therapy. In this perspective, we review the current state of undertreatment of patients at increased fracture risk and suggest possible short‐, intermediate‐, and long‐term approaches to address patient concerns, specifically those related to AFF risk. We suggest improved patient and physician education on prodromal symptoms, extended femur scans using dual‐energy X‐ray absorptiometry (DXA) to monitor patients on antiresorptive treatment, better identification of high‐risk patients perhaps using geometrical parameters from DXA and other risk factors, and more research on pharmacogenomics to identify risk markers. Although not the only impediment to appropriate treatment of osteoporosis, concern over AFFs remains a major issue and one that needs to be resolved for effective dissemination of existing treatments to reduce fracture risk. © 2016 American Society for Bone and Mineral Research.